Makna Teologis Respon Nabi Yunus Terhadap Panggilan Tuhan - Yimmy Iskandar (Jurnal Teologi Berita Hidup, 2019)
The Book Jonah is one of the books in the Old Testament. In this book, God tried to show His mercy to the people of Niniveh although they were living in many transgressions, and they repented after they heard Jonah’s messages. But in this book speaks more about Jonah’s journey to fulfill God’s calling in his life toward Niniveh, how Jonah responded to God. This research used data collection methods by searching literature such as books and journals related to the writer’s objectives. An analysis method is a qualitative approach with descriptive methods.  How Jonah responded to God’s calling were: running away, obeying but with dissatisfaction or grumbling, and obeying with fullest of understanding.  The implementation and conclusion from this analysis will teach us about the nature of God’s heart toward sinners and how we should respond to our calling from God to please Him.        Abstrak: Kitab Yunus adalah salah satu kitab dalam Perjanjian Lama. Dalam buku ini, Tuhan berusaha menunjukkan belas kasihan-Nya kepada orang-orang Niniveh meskipun mereka hidup dalam banyak pelanggaran, dan mereka bertobat setelah mendengar pesan Yunus. Tetapi dalam buku ini berbicara lebih banyak tentang perjalanan Yunus untuk memenuhi panggilan Allah dalam hidupnya menuju Niniveh, bagaimana Yunus menanggapi Allah. Penelitian ini menggunakan metode pengumpulan data dengan mencari literatur seperti buku dan jurnal yang berkaitan dengan tujuan penulis. Metode analisis adalah pendekatan kualitatif dengan metode deskriptif. Bagaimana Yunus menanggapi panggilan Allah adalah: melarikan diri, mematuhi tetapi dengan ketidakpuasan atau menggerutu, dan mematuhi dengan penuh pengertian. Implementasi dan kesimpulan dari analisis ini akan mengajarkan kita tentang sifat hati Allah terhadap orang berdosa dan bagaimana kita harus menanggapi panggilan kita dari Allah untuk menyenangkan Dia.